Governance, communication, and innovation in a knowledge intensive society - Siqueira, Sean, 1975-
"This book gathers the current research on knowledge management in governments, organizations, and institutions, and presents a compilation useful to academics, professionals, politicians, and policy makers invested in knowledge-intensive societies"--Provided by publisher.